2011
DOI: 10.1097/iae.0b013e3181ed8dc9
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Lattice Degeneration Characterized by Spectral Domain Optical Coherence Tomography

Abstract: PURPOSE-To utilize high-resolution spectral domain optical coherence tomography (SD-OCT) in the characterization of retinal and vitreal morphological changes overlying posterior lattice degeneration.METHODS-A cross-sectional, retrospective analysis was performed on 13 eyes of 13 nonconsecutive subjects with posterior lattice degeneration seen at the New England Eye Center, Tufts Medical Center between October 2009 and January 2010. SD-OCT images taken through the region of lattice degeneration were qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
1
12
0
1
Order By: Relevance
“…15 Similarly, a previous SD-OCT imaging series of peripheral degeneration found no vitreous attachment at the site of the two of the three retinal holes that were imaged. 7 In contrast, our OCT imaging detected vitreous attachment at the site of the retinal hole in 96.4% cases. This supports the recent SD-OCT imaging series of peripheral retina by Choudhry et al of that also found evidence of vitreoretinal attachment over retinal holes, and they postulated that the vitreous exerted traction on the inner retina at these sites.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…15 Similarly, a previous SD-OCT imaging series of peripheral degeneration found no vitreous attachment at the site of the two of the three retinal holes that were imaged. 7 In contrast, our OCT imaging detected vitreous attachment at the site of the retinal hole in 96.4% cases. This supports the recent SD-OCT imaging series of peripheral retina by Choudhry et al of that also found evidence of vitreoretinal attachment over retinal holes, and they postulated that the vitreous exerted traction on the inner retina at these sites.…”
Section: Discussionmentioning
confidence: 55%
“…15 In our series, we found lattice in a number of eyes whose retinal holes had associated RD or SRF and we know from histological and OCT work that vitreous is attached at the edge of lattice with an overlying vitreous bursa. 7,16 If a higher proportion of round holes imaged in our series were secondary to lattice degeneration, this may explain the higher rate of vitreous attachment.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These modalities may not fully capture the accurate structural relationship between vitreous and retina in vivo . Recently, some authors have reported SD-OCT imaging findings with SD-OCT of lattice degeneration [9, 10, 15], white without pressure [11], retinoschisis [4, 1618], and normative data for peripheral retinal thickness [19]. The authors recently observed retinal structural features on peripheral SD-OCT that were useful for clinical management and revealed some unexpected cross-sectional findings.…”
Section: Introductionmentioning
confidence: 99%
“…Недостаточно активное использование ОКТ при оценке ПВРД в немалой степени обусловлено тем, что ее технические возможности разработаны для заднего полюса глаза, в то время как ПВРД локализуются на экваторе и периферии глазного дна. Поэтому в литературе есть единичные работы, посвященные возможности ОКТ при исследовании зон ПВРД [7][8][9][10]. Нами разработана методика проведения ОКТ области экватора глазного дна, предназначенная для оценки анатомической картины ПВРД [11].…”
unclassified